2014
DOI: 10.1101/lm.035113.114
|View full text |Cite
|
Sign up to set email alerts
|

Appetitive cue-evoked ERK signaling in the nucleus accumbens requires NMDA and D1 dopamine receptor activation and regulates CREB phosphorylation

Abstract: Conditioned stimuli (CS) can modulate reward-seeking behavior. This modulatory effect can be maladaptive and has been implicated in excessive reward seeking and relapse to drug addiction. We previously demonstrated that exposure to an appetitive CS causes an increase in the activation of extracellular signal-regulated kinase (ERK) and cyclic-AMP responseelement binding protein (CREB) in the nucleus accumbens (NAc) of rats, and that CS-evoked ERK activation is critical for CS control over reward seeking. To elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 82 publications
2
21
0
Order By: Relevance
“…In addition, NMDARs can interact with dopamine‐type‐1 receptors (D1Rs), both through indirect interactions through second messengers (Cepeda et al ), and also through direct interactions that can be disrupted using a specific peptide. D1Rs and NMDARs interact in the NAc to promote methamphetamine reinstatement (Taepavarapruk et al ), as well as activation of downstream signaling in the NAc in response to reward‐predictive cues (Kirschmann et al ). However, studies using the peptide to disrupt direct D1R‐NMDAR interactions have produced mixed results, since D1R activation enhances NMDAR‐dependent LTP in hippocampal cultures (Nai et al ), while D1Rs inhibit NMDAR function (Lee et al ) and NMDAR‐dependent LTP at cortico‐NAc inputs after in vivo morphine (Zheng et al ).…”
Section: Interaction Of Nmdars With Other Receptor Typesmentioning
confidence: 99%
“…In addition, NMDARs can interact with dopamine‐type‐1 receptors (D1Rs), both through indirect interactions through second messengers (Cepeda et al ), and also through direct interactions that can be disrupted using a specific peptide. D1Rs and NMDARs interact in the NAc to promote methamphetamine reinstatement (Taepavarapruk et al ), as well as activation of downstream signaling in the NAc in response to reward‐predictive cues (Kirschmann et al ). However, studies using the peptide to disrupt direct D1R‐NMDAR interactions have produced mixed results, since D1R activation enhances NMDAR‐dependent LTP in hippocampal cultures (Nai et al ), while D1Rs inhibit NMDAR function (Lee et al ) and NMDAR‐dependent LTP at cortico‐NAc inputs after in vivo morphine (Zheng et al ).…”
Section: Interaction Of Nmdars With Other Receptor Typesmentioning
confidence: 99%
“…For example, administration of D1R agonists has been reported to increase phosphorylation levels of ERK selectively in the NAc and PFC, while D2 agonists had no effect (Xue et al, 2015 ). In terms of reward-related behavioral processing, Kirschmann et al ( 2014 ) reported that the ability of reward-related conditioned stimuli to activate ERK signaling in the NAc, was mediated through a D1R-NMDA dependent mechanism. Bertran-Gonzalez et al ( 2008 ) reported that psychostimulant-induced activation of ERK phosphorylation in the NAc was confined exclusively to D1R-containing striatal neurons, providing yet further evidence for functional D1R-mediated selectivity over downstream modulation of ERK phosphorylation events, at least in the context of drug-related effects in the mesolimbic system.…”
Section: Molecular Memory Substrates Controlling Opiate Memory Formatmentioning
confidence: 99%
“…Drugs targeting ERK, CREB, NPY and POMC expression have been suggested as clinical pharmacotherapy for the improvement of some brain diseases and obesity. Previous findings indicated that ERK/CREB signalling participated in regulating anxiety‐like behaviour induced by the anorectic neuropeptide nesfatin‐1 (Ge et al, ) and that the activation of the dopamine D 1 receptor/ERK/CREB signal pathway in the nucleus accumbens played a critical role in the control of reward‐seeking behaviour (Kirschmann et al, ). Thus, ERK/CREB signalling may be a target for the improvement of some brain‐associated behavioural disorders.…”
Section: Discussionmentioning
confidence: 99%